Anti-Inflammatory and Neuromodulatory Effects Induced by Tanacetum parthenium Water Extract: Results from In Silico, In Vitro and Ex Vivo Studies - Recinella, Lucia (Molecules, 2020)
Tanacetum parthenium (feverfew) has traditionally been employed as a phytotherapeutic remedy in the treatment of migraine. In this study, a commercial T. parthenium water extract was investigated to explore its anti-inflammatory and neuromodulatory effects. Isolated mouse cortexes were exposed to a K(+) 60 mM Krebs-Ringer buffer and treated with T. parthenium water extract. The prostaglandin E(2) (PGE(2)) level, brain-derived neurotrophic factor (BDNF), interleukin-10 (IL-10), and IL-1β gene expression were evaluated in the cortex. The effects on dopamine (DA) release and dopamine transporter (DAT) gene expression were assayed in hypothalamic HypoE22 cells. A bioinformatics analysis was conducted to further investigate the mechanism of action. The extract was effective in reducing cortex PGE(2) release and IL-1β gene expression. In the same experimental system, IL-10 and BDNF gene expressions increased, and in HypoE22 cells, the extract decreased the extracellular dopamine level and increased the DAT gene expression due to the direct interaction of parthenolide with the DAT. Overall, the present findings highlight the efficacy of T. parthenium water extract in controlling the inflammatory pathways that occur during cortical-spreading depression. Additionally, the inhibition of the hypothalamic DA release observed in this study further supports the role of dopaminergic pathways as key targets for novel pharmacological approaches in the management of migraine attacks.